RESPON TANAMAN JAGUNG (Zea mays L.) NK6172 PERKASA TERHADAP PEMBERIAN BEBERAPA JENIS PUPUK ORGANIK - Abdul Haris; Bakhtiar Ibrahim; Syahrul Syahrul (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2023)
Syahrul Growth Response of Corn Plants (Zea mays L.) NK6271 Perkasa Against Several Types of Organic Fertilizers. Abdul Haris as a supervisor I and Bakhtiar Ibrahim as supervisor II. This study aims to determine the growth response of maize (Zea Mays L.) NK6271 Perkasa to several types of organic fertilizers. This research was conducted on corn farmers' land, Lea Village, Tellussiattinge District, Bone Regency, South Sulawesi Province. This research started from August to November 2022. This research was arranged using a Randomized Block Design (RBD). The treatment consisted of 5 levels, namely without organic fertilizer (control), 3 kg/plot cow manure, 3 kg/plot chicken manure, 3 Lite/plot liquid bio-slurry, and 3 kg/plot goat manure. Each treatment was repeated 3 times to obtain 15 experimental units. The results showed that the application of organic fertilizer had a significant effect on cob diameter, the number of cob seeds, and had a significant effect on the weight of 100 seeds in the NK6271 Perkasa variety of maize.